Occurrence of true branches in Rhizoclonium (Cladophorales, Ulvophyceae) and the reinstatement of Rhizoclonium pachydermum Kjellman - Zhao, Zhi-Juan; Zhu, Huan; Hu, Zheng-Yu; Liu, Guo-Xiang (Phytotaxa, 2014)
The phylogenetic position of the freshwater green alga Rhizoclonium pachydermum (Ulvophyceae: Cladophorales) was investigated using nuclear 18S rRNA gene and internal transcribed spacer 2 (ITS2) sequences. This alga has been referred to as Cladophora pachyderma. Based on its morphology, it was formerly classified in the section Affines in the genus Cladophora. However, this classification was not supported by the current phylogenetic analyses, where Rhizoclonium pachydermum formed a well-supported clade with other Rhizoclonium species. We consider that Rhizoclonium possesses real branches and the most important criteria that characterize the genus are: long unbranched filaments only with rhizoid branches, or only branched at the basal region of the thallus; and cylindrical cells with few or limited numbers of nuclei.